Structural Equation Modelling of Determinants of Buyer–Supplier Relationship Improvement Strategies: Case of Indian Manufacturing Firms. (June 2016) - Joshi, Sarang Prakashrao; Verma, Rakesh; Bhasin, Harsh Vardhan; Kharat, Manoj Govind; Kharat, Mukesh Govind
Recently, many organisations have recognised that development of supplier and buyer relationship improvement is becoming necessary to establish strong and mutually beneficial long-term relationships in improving performance across the supply chain, generating greater cost efficiency and enabling the business to grow and develop. The current study proposes a framework for buyer–supplier relationship improvement (BSRI) strategy and tests the same using structural equation modelling (SEM). Result indicates that BSRI can be improved under the condition of supplier development practices (SDP) and buyer–supplier relationship practices (BSRP). SDP are further driven by productive measure (PM) and competitive pressure (CP), whereas the impact of customer uncertainty (CU) turned out insignificant. The study results demonstrate that profitability (PR) can be improved by achieving competitive advantages (CA) through BSRI. CA includes operational effectiveness, innovation (INV), technology adaption (TAD) and risk minimisation (RIM). A survey response of 512 different manufacturing firms of India was used for data analysis. Initially, exploratory factor analysis (EFA) is performed for exploring the factor followed by confirmatory factor analysis (CFA), for confirmation and construct validity. Findings from the study revealed that linking of SDP with BSRI is necessary from buyer side along with consideration of supplier's perspective to achieve CA, which will lead towards enhanced PR.